2010
DOI: 10.1007/s10665-010-9364-1
|View full text |Cite
|
Sign up to set email alerts
|

Motion of paramagnetic particles in a viscous fluid under a uniform magnetic field: benchmark solutions

Abstract: Numerical simulations of the two-dimensional motion of multiple paramagnetic particles suspended in a viscous fluid subjected to a uniform magnetic field are presented. Both the magnetic field and flow field can be described efficiently with simple series in local coordinates attached to each particle. The coefficients of the series can be obtained with fast convergence when only a few leading coefficients are treated implicitly. Numerical results for the flow field are validated by comparing the data with tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 19 publications
4
23
0
Order By: Relevance
“…To validate the numerical method proposed in the present study, we perform numerical simulations on the two-dimensional particle motion and fluid flow for the case of two and three paramagnetic particles suspended in a square cavity filled with a nonmagnetic viscous fluid subjected to an external uniform magnetic field and then compare their results qualitatively with the finite-element solution of Kang et al [2] and quantitatively with the semi-analytical solutions of Suh and Kang [9]. Here, all the particles are of two-dimensional circular cylinder with the same radius, a = 1.…”
Section: Validation and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To validate the numerical method proposed in the present study, we perform numerical simulations on the two-dimensional particle motion and fluid flow for the case of two and three paramagnetic particles suspended in a square cavity filled with a nonmagnetic viscous fluid subjected to an external uniform magnetic field and then compare their results qualitatively with the finite-element solution of Kang et al [2] and quantitatively with the semi-analytical solutions of Suh and Kang [9]. Here, all the particles are of two-dimensional circular cylinder with the same radius, a = 1.…”
Section: Validation and Discussionmentioning
confidence: 99%
“…The proposed numerical method is validated by applying it to the two-dimensional motion of two and three particles suspended in a nonmagnetic viscous fluid inside a square cavity subjected to an external uniform magnetic field and then comparing the results with the semi-analytical benchmark solutions of Suh and Kang [9] and the finite-element solution of Kang et al [2]. In the present study, therefore, we will focus ourselves mainly on the validation of the proposed method rather than on the detailed explanation of interesting physical phenomena or fundamental mechanism because most of them were already fully discussed in Kang et al [2] and Suh and Kang [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though modeling and simulation are employed to investigate the self-assembly and the dynamics of Janus particles [26][27][28][29][30][31], further studies are still required to understand the magnetic interaction lying behind the formation of various self-assembly structures and the fluid flow induced by the actuated particles. Direct numerical simulation schemes [32][33][34][35][36][37], which have been developed to solve particulate flows with isotropic magnetic particles, are promising options in tackling particulate flows with Janus magnetic particles if they are enhanced to take into account the magnetic anisotropy of the particles.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that such a time-varying magnetic field enhances mixing, and switching the spinning direction further improves the mixing rate. It is well known that when a magnetic field is applied to a fluid containing scattered paramagnetic particles, they tend to align in a chain configuration (see e.g., [58][59][60]). Obviously the linear structure of particles should be more effective than the isolated ones in fluid stirring for mixing.…”
Section: Stirring By Particlesmentioning
confidence: 99%